Factors influencing intention for fraud in financial reporting among muslim accounting practitioners in the Malaysian banking industry - Yunita binti Awang (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Fraud is a global business problem causing significant ethical dilemmas for businesses and harmful to capital market participants. Fraud gives rise to severe financial losses. Fraud in financial reporting is the intentional misstatement of financial information to mislead the financial statement's users. It threatens investors' confidence in published financial statement. Fraudsters are commonly involved in finance or finance-related functions for reasons of unattainable high earnings projection, personal gain and weakening moral values. Fraud is indeed a very difficult misconduct to prove as it is normally concealed, not easily measurable or detectable. The main objective of this study is to examine the factors influencing intention for fraud in financial reporting among Muslim accounting practitioners in a highly regulated Malaysian banking industry. The intention rather than actual occurrence of fraud in financial reporting is examined, as the likelihood of performing behaviour depends on the level of behavioural intention. This study adopts a mixed method approach that employs aspects of both quantitative and qualitative procedures involving self-administered questionnaire and semi-structured interviews. A total of 121 respondents were involved in the survey and partial least square structural equation modelling was used in analysing the quantitative data. The results indicate that attitude, subjective norm and ethical judgments are influential factors, whereas perceived behavioural control, Islamic religiosity and adherence to Islamic professional ethics are not influential factors in the intention for financial reporting fraud. Meanwhile, twenty interviewees participated in the semi-structured interviews that provide supports to all significant survey findings but partially support the results on perceived behavioural control and contradict the findings on the Islamic religiosity and adherence to Islamic professional ethics. The input gathered from the semi-structured interviews was analysed and categorised into meaningful perspectives, which led to three new emerging themes of high regulation, the tone at the top and secular worldview. This study contributes in testing the extended Theory of Planned Behaviour that incorporates ethics factor and religious values based on Rest's four component model and Hunt and Vitell's model. Although the theories are developed in the west, the variables such as attitude, subjective norms, perceived behavioural control and ethical judgment are applicable to the Islamic environment. However, the variables of Islamic religiosity and Islamic professional code of ethics are specifically tailored for the Muslims due to the differences between the Western and Islamic environment. This study specifically highlights the influence of Muslim accounting practitioners' Islamic worldview on fraud intention. The emerging factors that influence intention provide new perspectives to auditors, top management and regulators within the industry in developing strategies to curb the intention for fraud in financial reporting.